Transition-metal/Lewis acid free synthesis of acyl benzothiophenes via C-C bond forming reaction - Pal, Sarbani; Khan, Mohammad Ashrafuddin; Bindu, P.; Dubey, P. K. (Beilstein Journal of Organic Chemistry, 2007)
A simple and single-step synthesis of 2- and 3-acyl substituted benzothiophenes has been described via environmentally benign acylation of benzothiophene with in situ generated acyl trifluoroacetates. Both aliphatic and aromatic carboxylic acids participated in trifluoroacetic anhydride/phosphoric acid mediated C-C bond forming reactions under solvent-free conditions affording acyl benzothiophenes in good overall yields.